âPIAMAN DALAM RITMEâ (Irama Kehidupan Laki-laki dalam Komposisi Musik Inovatif) - Jaya, Susandra (Ekspresi Seni, 2011)
Pariaman has a culture that does not belong to other regions, that is, the culture of âBajapuikâ. It is a proposal from the bride to the groom where the bride family has to present some money (in the form of gold coins) or other valuable things to the bride family; it is called uang jemputan (drowsy). The presentation of drowsy is called bajapuik. It is a requirement that must be fulfilled by the bride familty before the marriage is to take place. It is also a form of respect shown by the bride family to the groom family. A problem may occur in bajapuik tradition when the bride comes from other regions outside Pariaman. This is a phenomenon that will be expressed in a music composition